2013
DOI: 10.1289/ehp.1205223
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Older Americans: State of the Science

Abstract: Background: Older adults make up 13% of the U.S. population, but are projected to account for 20% by 2040. Coinciding with this demographic shift, the rate of climate change is accelerating, bringing rising temperatures; increased risk of floods, droughts, and wildfires; stronger tropical storms and hurricanes; rising sea levels; and other climate-related hazards. Older Americans are expected to be located in places that may be relatively more affected by climate change, including coastal zones and large metro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
135
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(150 citation statements)
references
References 60 publications
7
135
0
8
Order By: Relevance
“…Consistent with other studies, we found that the elderly people had a higher morbidity and mortality rate of heatrelated illness during extreme heat days, which may be because they are weak, living in poverty, isolated, or have difficulty getting help (Gamble et al 2013). In this analysis, males seem to be more vulnerable than females to heat effects, which may be because males are more likely to be engaged in the occupational exposure to high temperatures (Bai et al 2014b).…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with other studies, we found that the elderly people had a higher morbidity and mortality rate of heatrelated illness during extreme heat days, which may be because they are weak, living in poverty, isolated, or have difficulty getting help (Gamble et al 2013). In this analysis, males seem to be more vulnerable than females to heat effects, which may be because males are more likely to be engaged in the occupational exposure to high temperatures (Bai et al 2014b).…”
Section: Discussionsupporting
confidence: 89%
“…The regression analysis equally showed that while climate change accounted for about 12% of the variations in the prevalence of climate-related diseases in the study area between 2001 and 2015, the contributions of fluctuations in the amount of precipitation were higher. These findings are not largely different from those of Schwartz (1994), Schwartz and Morris (1995), Filliberto et al (2010) and Gamble et al (2013).…”
Section: Discussionsupporting
confidence: 46%
“…The climate-related diseases reviewed are those affecting the lungs; asthma, bronchitis and pneumonia, febrile illnesses; malaria, typhoid, yellow fever and dengue fever, waterborne diseases; cholera and diarrhea as well as heart (high blood pressure), skin and eye diseases with environmental prognosis. The impacts of temperature and rainfall variations on diseases are well documented in the literature (Adeboyejo et al, 2012;Gamble et al, 2013;Adewoyin, 2015 for instance).…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Studies have shown that the incidence of strokes is more in extreme weather conditions [47] . The elderly are readily susceptible to these tumultuous conditions [48] and hence they might be subject to higher number stroke attacks in recent times.…”
Section: Discussionmentioning
confidence: 99%